Impact of Fiscal Decentralization on Buoyancy of Services Tax in Khyber Pakhtunkhwa - Atif, Muhammad; Nazir, Naila (Pakistan Journal of Humanities and Social Sciences, 2023)
The present research investigates the impact of fiscal decentralization on services tax buoyancy in province Khyber Pakhtunkhwa covering time series data from 2001 to 2021. Chow Break Point test for detecting structural break was applied and found structural break in the year 2014 which coincided with the year of devolution. The break in the data was taken care by Binary Dummy variable as an intervention and interaction terms in the model. The results of segmented intervention model illustrated that the estimated tax buoyancy have positive and more than unitary effects during post-tax devolution period. While, the services tax was non-buoyant, at the time FBR was collecting the said tax. However, despite having buoyant tax, KPRA due to complexities in post devolved tax system have missed its revenue targets and was unable to explore services sector up to optimum potential. Based on the findings, the study recommends broadening of tax base, documentation to bring more taxpayers in the tax net and enhancement in tax administration to achieve revenue targets and explore un-tax services tax in the province.